2014
DOI: 10.1038/nchem.1947
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of most polyene natural product motifs using just 12 building blocks and one coupling reaction

Abstract: The inherent modularity of polypeptides, oligonucleotides, and oligosaccharides has been harnessed to achieve generalized building block-based synthesis platforms. Importantly, like these other targets, most small molecule natural products are biosynthesized via iterative coupling of bifunctional building blocks. This suggests that many small molecules also possess inherent modularity commensurate with systematic building block-based construction. Supporting this hypothesis, here we report that the polyene mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
136
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(141 citation statements)
references
References 51 publications
1
136
0
4
Order By: Relevance
“…The key for understanding these fungal PKS modules is their ability to operate iteratively. 37 The exact mechanism of chain extension is largely unknown but their impressive iterative power is demonstrated in the reconstitution of the PKS of dihydromonacolin (46). Compound 46 is a precursor of the hypolipidemic drug lovastatin 47 that is produced by Aspergillus terreus (Scheme 11).…”
Section: Strategy 3: Iterative Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key for understanding these fungal PKS modules is their ability to operate iteratively. 37 The exact mechanism of chain extension is largely unknown but their impressive iterative power is demonstrated in the reconstitution of the PKS of dihydromonacolin (46). Compound 46 is a precursor of the hypolipidemic drug lovastatin 47 that is produced by Aspergillus terreus (Scheme 11).…”
Section: Strategy 3: Iterative Reactionsmentioning
confidence: 99%
“…In a remarkable recent paper the Burke group demonstrated that 12 different MIDA building blocks are in principal sufficient to iteratively prepare about 75% of all known polyene natural products. 46 4.4 Strategy 4: spatial compartmentation of individual steps -from polyketide biosynthesis to ow chemistry The fourth strategy of nature's multistep biosynthesis is spatial compartmentation which can be discussed from two perspectives, a microscopic 47 and a molecular view. Microscopic compartmentation refers to cell organelles which have individual metabolic functions and which are characterised by different chemical conditions with respect to enzyme compositions and pH.…”
Section: Strategy 3: Iterative Reactionsmentioning
confidence: 99%
“…Due to the broad utility of boronic acids as starting materials in a number of key transformations, this approach could open up opportunities for new iterative C-C bond forming events which complement other elegant approaches. 2,3,[22][23][24][25][26] Figure 1|Prior work on boronic acids-diazo coupling and development of an iterative reaction strategy. a) Proposed mechanism for the combination of diazo species and boronic acids, followed by either protodeboronation and oxidation (previous work), or exploration of new reactivity of transient boronic acid species; b) mechanistic description for the sequential generation of the single addition product 3a and the double addition and generation of the corresponding products 5a1 and 6a1 via subsequent trapping with pinacol; c) setup for the generation, storage and reaction of the diazo species with boronic acids under full machine assistance (description of the setup can be found within the Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…13 Use of a slow-release BMIDA process limits the boronic acidÕs exposure and thus the potential for protodeboronation. This strategy has enabled the concise and flexible synthesis of a wide range of polyene natural products from a small number of halovinyl BMIDA building blocks and is a potent example of the utility of protected boronic acids to enable chemoselective transmetallation in the context of complex molecule synthesis (Scheme 2).…”
mentioning
confidence: 99%